Journal of Orthopaedics and Traumatology Official Journal of the Italian Society of Orthopaedics and Traumatology - d'Imporzano, Marco
The Journal of Orthopaedics and Traumatology, the official open access peer-reviewed journal of the Italian Society of Orthopaedics and Traumatology, publishes  original papers reporting basic or clinical research in the field of orthopaedic and traumatologic surgery, as well as systematic reviews, brief communications, case reports and letters to the Editor. Narrative instructional reviews and commentaries to original articles may be commissioned by Editors from eminent colleagues. The Journal of Orthopaedics and Traumatology aims to be an international forum for the communication and exchange of ideas concerning the various aspects of orthopaedics and musculoskeletal trauma.